2017
DOI: 10.1007/s11664-017-5777-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Ni on Bi2Te3 and Interfacial Reaction Between Sn and Ni-Coated Bi2Te3

Abstract: Bismuth-telluride (Bi 2 Te 3 )-based compounds are common thermoelectric materials used for low-temperature applications, and nickel (Ni) is usually deposited on the Bi 2 Te 3 substrates as a diffusion barrier. Deposition of Ni on the p-type (Sb-doped) and n-type (Se-doped) Bi 2 Te 3 substrates using electroplating and interfacial reactions between Sn and Ni-coated Bi 2 Te 3 substrates are investigated. Electrodeposition of Ni on different Bi 2 Te 3 substrates is characterized based on cyclic voltammetry and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…First, for the Bi 2 Te 3 -based TE module, the interfacial reactions include the reaction of the Ni barrier layer with the solder layer and the reaction of Ni with the TE leg. According to previous studies, 29,30 it was reported that the formation rate of the Ni 3 Sn 4 reactive layer between Ni and the solder layer is about 5 μm/1000 h at a temperature of 200 °C. The generation rate of the reactive layer between Ni and the ptype thermoelectric leg at a temperature of 250 °C is about 0.4 μm/day, and it is 0.9 μm/day for the n type.…”
Section: Basic Assumptionsmentioning
confidence: 96%
“…First, for the Bi 2 Te 3 -based TE module, the interfacial reactions include the reaction of the Ni barrier layer with the solder layer and the reaction of Ni with the TE leg. According to previous studies, 29,30 it was reported that the formation rate of the Ni 3 Sn 4 reactive layer between Ni and the solder layer is about 5 μm/1000 h at a temperature of 200 °C. The generation rate of the reactive layer between Ni and the ptype thermoelectric leg at a temperature of 250 °C is about 0.4 μm/day, and it is 0.9 μm/day for the n type.…”
Section: Basic Assumptionsmentioning
confidence: 96%
“…The design of TEG can usually be categorized into in-plane and cross-plane structures [26]. Many works have been reported on cross-plane bismuth telluride based thin film through electrodeposition [27], screen printing [28], brush-painting [29,30] and inkjet printing [31]. In comparison, an in-plane TEG structure is mechanically stronger and more flexible and conformable over a hot surface [32][33][34][35].…”
Section: Toc Graphics Introductionmentioning
confidence: 99%
“…Ni can both improve the bonding strength between solder and substrate and block the diffusion of solder to the substrate. [26][27][28][29][30] In addition, the interfacial products formed by Ni and Bi 2 Te 3 -based TE materials are mostly binary Ni x Te y intermetallic compounds (such as NiTe, 31,32 NiTe 2, 32,33 Ni 3 Te 2,…”
Section: Introductionmentioning
confidence: 99%